Two-year temporal response of benthic macrofauna and sediments to hypoxia in a tropical semi-enclosed bay (Cienfuegos, Cuba) - Díaz Asencio, Lisbet (2016)
Hypoxia is the depletion of dissolved oxygen below 2 mg O2/L. Relatively few studies on hypoxia and its effects on benthic macrofauna have been done in tropical marine ecosystems. This study describes the temporal response of the water column, sediments and macrofauna to seasonal hypoxia in a semi-enclosed bay (Cienfuegos, Caribbean Sea). The Calisito site was sampled monthly from June 2010 until February 2012, yielding 21 sampling times. At each sampling event water and sediment samples were collected for measuring the abiotic variables (temperature, salinity, dissolved oxygen, nutrients, redox potential discontinuity, silt/clay and organic matter content) and macrofauna (abundance and species richness). Temperature and surface salinity followed a typical temporal pattern during the summer/rainy and the winter/dry periods. Salinity stratification occurred in the rainy period, lasting three months in 2010 and six months in 2011. The bottom water dissolved oxygen indicated hypoxic and anoxic events during the wet periods of 2010 and 2011 associated with salinity stratification, low hydrodynamics and oxidation of the accumulated organic matter. Over the study period, 817 individuals were collected and identified. Polychaetes were the dominant group in terms of abundance (57 % of total) followed by mollusks (41%). Hypoxia (and occasionally anoxia) caused strong deleterious effects on the abundance and species richness of macrofaunal communities in the study site. The most abundant polychaetes were opportunistic species with high tolerance to hypoxic conditions: Prionospio steenstrupi, Polydora sp.and Paraprionospio pinnata. Most of them colonized relatively fast once hypoxia ended. Persistent species such as Caecum pulchellum and Parvanachis obesa were present during hypoxia with fluctuating densities and apparently recover to higher abundances when normoxic conditions are re-established. Macoma tenta and Tellina consobrina colonized approximately 1-2 months later than the first polychaete peak during normoxia. Probably, the deleterious effects of hypoxia on the macrofauna were intensified by negative interspecific relationships such as competition by suitable space and predation. The recolonization of macrofauna depended possibly on local transport by currents within the bay because the connection with the Caribbean Sea is relatively limited. In summary, seasonal hypoxia in Cienfuegos Bay influences the water and sediment geochemistry and reduces both the abundance and diversity of macrofauna.